ANALYZING LITERACY BEHAVIOURS PRESENTED IN AN INDONESIAN AND AMERICAN TEEN MAGAZINE - Liah Rosdiani Nasution (IAIN Padangsidimpuan, 2022)
AbstractThis article discusses the comparison of adolescent literacy attitudes in Indonesia and the United States which is described through the advertising content published in each magazine which is studied based on a qualitative approach. In this project, one Indonesian magazine (Annida) and one United States magazine (Discovery girls) were used as samples. Both are young women's magazines that have similar components such as reader letters, short stories, fashion tips, consulting, and advertising. The reason for sampling these two magazines is because of their availability and the purpose is to compare the advertising components in the two magazines and see the frequency of categories related to literacy behavior such as books, magazines or novels and other types of literary texts. Although these two magazines do not fully represent Indonesian youth and American youth, the advertisements in both magazines can help explain the reality of literacy behavior in the two countries in question, Indonesia and the United States.AbstrakArtikel ini membahas tentang perbandingan sikap literasi remaja di Indonesia dan di Amerika Serikat yang digambarkan melalui konten iklan yang dimuat di masing-masing majalah yang dikaji berdasarkan pendekatan kualitatif. Dalam proyek ini, satu majalah Indonesia (Annida) dan satu majalah Amerika Serikat (Discovery girls) digunakan sebagai sample. Keduanya adalah majalah remaja putri yang memiliki komponen serupa seperti surat pembaca, cerita pendek, kiat fashion, konsultasi, dan iklan. Alasan pengambilan sampel kedua majalah ini adalah karena ketersediaannya serta tujuan untuk membandingkan komponen iklan di kedua majalah dan melihat frekuensi kategori terkait perilaku literasi seperti buku, majalah atau novel dan jenis teks literatur lainnya. Meskipun kedua majalah ini tidak sepenuhnya mewakili remaja Indonesia dan remaja Amerika, iklan di kedua majalah tersebut dapat membantu menjelaskan realitas perilaku literasi di kedua negara yang dimaksud, Indonesia dan Amerika